Three-Dimensional Analysis of Craniofacial Structures of Individuals With Nonsyndromic Unilateral Complete Cleft Lip and Palate. Issue 1 (January 2021) - Parveen, Shahistha; Husain, Akhter; Johns, Gejo; Mascarenhas, Rohan; Reddy, Srinivas Gosla
Abstract : Abstract: Cleft lip and palate (CLP) is one of the most common congenital deformities. Primary surgeries at an early age result in scar formation, which may impede the growth of craniofacial structures of the maxilla. Orthodontist's role in the management of individuals with CLP is important and starts from the time of birth. The knowledge of craniofacial structures in individuals with a cleft is essential for treatment planning. The purpose of this study was to analyze and compare craniofacial structures of cleft and noncleft side of individuals with non-syndromic unilateral complete cleft lip and palate (NSUCCLP) using cone-beam computed tomography (CBCT). CBCT scans of individuals with NSUCCLP (n = 42) were retrieved from the databases of two cleft centers, which followed the same protocols for timing and type of primary surgeries and secondary alveolar bone grafting (SABG). DICOM files of CBCT scans were integrated into Dolphin 3D software, and analysis was carried out in multiplanar views. The craniofacial structures of individuals with NSUCCLP were analyzed using fourteen parameters. Measurements were also recorded between the cleft and noncleft sides for comparison. The volume of the maxilla was generated by isolating it from adjacent structures on a 3D reconstructed model. MAWC, MAWPM1, MAWPM2, MAWM1, and MV of the cleft side was less than noncleft side ( P < 0.05). MHP @ N Aper is less on the noncleft side ( P < 0.05). There is an asymmetry of structures around the dentoalveolar and nasal region; however, asymmetries were not affected at deeper structures of the craniofacial region of individuals with NSUCCLP. Abstract : Supplemental Digital Content is available in the text